2022
DOI: 10.3390/medicina59010064
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Care: A Screening on Primary Care Providers’ Attitude and Practice in Riyadh, Saudi Arabia

Abstract: Background and Objectives: Diabetic foot (DF) disease is one of the myriad complications of diabetes. Positive outcomes are expected through a multidisciplinary approach as provided by primary care providers (PCPs). This study aimed to assess the knowledge of DF and attitude of physicians in primary healthcare settings toward DF diagnosis and prevention in Saudi Arabia. Materials and Methods: This observational cross-sectional study used a self-administered questionnaire that was completed by family medicine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…The susceptible people are those whose feet are sensitive to injury caused by unfitted footwear that may affect long-term foot health, such as chronic patients and older peo-ple [14]. Alsheikh et al [15] researched the need for primary healthcare based on diabetic foot conditions. They found that, recently, patients have been less cared for in terms of foot health and that there is a need for further study to fill this gap.…”
Section: Feet Detectionmentioning
confidence: 99%
“…The susceptible people are those whose feet are sensitive to injury caused by unfitted footwear that may affect long-term foot health, such as chronic patients and older peo-ple [14]. Alsheikh et al [15] researched the need for primary healthcare based on diabetic foot conditions. They found that, recently, patients have been less cared for in terms of foot health and that there is a need for further study to fill this gap.…”
Section: Feet Detectionmentioning
confidence: 99%
“…Selain itu sebanyak 42 subjek (89,36)% belum mengetahui bahwa pasien DM dianjurkan untuk memeriksa kaki setiap hari. Dalam penelitian yang dilakukan oleh Alsheikh et al (2022) menyebutkan bahwa salah satu item dalam perawatan kaki pasien DM adalah melakukan pemeriksaan kaki rutin. Demikian juga yang disebutkan dalam guadeline IWGDF (Schaper et al, 2020).…”
Section: Karakteristik Pengetahuan Subjek Sebelum Diberikan Edukasiunclassified
“…of the participants (35.5%) did not examine the high-risk patient's foot regularly or at every visit (33). Previous studies have shown that regular foot screening and evaluation can increase the patient's knowledge and education about foot care and prevention of diabetic foot ulcers, which highlights the importance of diabetic foot screening (34).…”
mentioning
confidence: 99%